2024
DOI: 10.1007/s10120-023-01453-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of preoperative chemotherapy with docetaxel, oxaliplatin, and S-1 for gastric cancer with extensive lymph node metastasis (JCOG1704)

Yukinori Kurokawa,
Yuichiro Doki,
Ryo Kitabayashi
et al.

Abstract: Background The prognosis for marginally resectable gastric cancer with extensive lymph node metastasis (ELM) remains unfavorable, even after R0 resection. To assess the safety and efficacy of preoperative docetaxel, oxaliplatin, and S-1 (DOS), we conducted a multicenter phase II trial. Methods Eligibility criteria included histologically proven HER2-negative gastric adenocarcinoma with bulky nodal (bulky N) involvement around major branched arteries or par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other experiences, mainly from Japan, have reported similar results. In particular, the JCOG 1704 trial enrolled 47 patients who received three cycles of docetaxel, oxaliplatin, and S-1 followed by D2plus lymphadenectomy: postoperative morbidity for grade III or higher was 11%, with no postoperative deaths [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other experiences, mainly from Japan, have reported similar results. In particular, the JCOG 1704 trial enrolled 47 patients who received three cycles of docetaxel, oxaliplatin, and S-1 followed by D2plus lymphadenectomy: postoperative morbidity for grade III or higher was 11%, with no postoperative deaths [21].…”
Section: Discussionmentioning
confidence: 99%
“…After D2plus lymphadenectomy, a median (IQR) of 39 (30-56) total lymph nodes were removed; of these, a median of 25 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) total lymph nodes were removed at the first level (stations 1 to 7), 6 (3-10) at the second level (stations 8 to 12), and 7 (4-13) at the third level (stations 8p, 12 b/p, 13, and 16) (Figure 1).…”
Section: Surgical Treatment and Lymphadenectomymentioning
confidence: 99%
See 1 more Smart Citation
“…The longer term results of this trial have since been reported and included a significantly higher 5-year OS rate in the group that received preoperative DOS (66.8 vs 63.0%) [ 10 ]. In Japan, where only gastric cancer has been treated, the efficacy of DOS therapy has been reported with a promising pathological complete response rate (24%) [ 11 ]. Although such promising regimens of FLOT and DOS have been reported, there are currently few reports on safety and efficacy in Japanese patients with EGJ-AC.…”
Section: Introductionmentioning
confidence: 99%